Transformers. Age of extinction [videorecording (Blu-Ray)] - Wahlberg, Mark, 1971-; Tucci, Stanley (Paramount, 2014)
The world was saved after an epic battle that left a great city torn. As humanity picks up the pieces, a shadowy group reveals itself in an attempt to control the direction of history, while an ancient, powerful new menace sets Earth in its crosshairs. With help from a new cast of humans, Optimus Prime and the Autobots rise to meet their most fearsome challenge yet. In an incredible adventure, they are swept up in a war of good and evil, ultimately leading to a climactic battle across the world.